N. F. S. Grundtvigs foredrag i Danske Samfund 21. september 1841 - Overgaard, Ulrik (Grundtvig-Studier, 2009)
N. F. S. Grundtvigs foredrag i Danske Samfund 21. september 1841 [N. F. S. Grundtvig's lecture to the Danske Samfund on 21 September 1841] By Ulrik Overgaard The contemporary school system is the topic of Grundtvig’s lecture to the Danske Samfund on 21 September 1841. Grundtvig emphasises in the first place the necessity of compulsory school attendance (introduced in Denmark in 1814). He argues, though, that poor schools are much worse than none and that the number of bad schools is disturbingly high. Grundtvig then gives the definition of a good school: In a fine school the teachers should be vivid and engaged people, and the teaching methods should encourage the children to learn how to live a useful, wise and enjoyable life. Unfortunately, the contemporary schools do not fulfil this goal. On the contrary, the methods are characterised by punishments and rote learning, i.e. the teaching is dead. The only exceptions are the few schools where the schoolmaster himself is a living human being who wants to talk with the pupils and respect their opinions.